Characterization of circulating extracellular traps and immune responses to citrullinated LL37 in psoriasis - Martín Monreal, María Teresa; Kvist-Hansen, Amanda; Massarenti, Laura; Steffensen, Rudi; Loft, Nikolai; Hansen, Peter Riis; Ødum, Niels; Skov, Lone; Nielsen, Claus H. (Frontiers in Immunology, 2023)
The DNA-binding peptide LL37 is a suspected autoantigen in psoriasis. It can be found in neutrophil extracellular traps (NETs) which have been suggested to play a role in the pathogenesis of the disease. Citrullination, the conversion of peptidyl-arginine into peptidyl-citrulline, can be implicated in the formation of NETs. We hypothesized that citrullination increases LL37 immunogenicity and that NETs are a source of LL37.We aimed to characterize cytokine responses of B cells and T cells to native and citrullinated LL37 (citLL37) and determine the prevalence and composition of circulating NETs in patients with psoriasis and healthy blood donors (HDs).Mononuclear cells (MNCs) and serum were isolated from 20 HDs and 20 patients with psoriasis. The MNCs were stimulated with native LL37 and citLL37 and the proportion of cytokine-positive B cells and T cells was determined by flow cytometry. Circulating antibodies against native LL37 and citLL37 as well as circulating NETs were measured by ELISA, as was the content of LL37, citLL37, and IgG in the NETs.CitLL37, but not native LL37, induced IFN--production by T cells and B cells from psoriasis patients, as well as IL-10-production by the patients' CD4 + T cells. Serum from 40% of patients and 55% of HDs contained circulating NETs, of which 63% and 27%, respectively, contained LL37. Only two patients had NETs containing citLL37 and IgG antibodies were found in NETs from three patients and one HD. Post-hoc analysis of the cytokines produced by B cells and T cells after stimulation with citLL37 revealed two clusters of patients consisting of 10 high-responders and 9 low-responders. The high-responders were those that had circulating NETs in combination with an earlier age of onset of the disease.Citrullinated but not native LL37 elicits IFN--responses by T cells and B cells from psoriasis patients, particularly those with circulating NETs and early disease onset, suggesting a role of citLL37 as an autoantigen in this subgroup of patients.